Prevalence and classification of rhinitis in the elderly: a nationwide survey in Portugal. Issue 9 (6th August 2013) - Morais‐Almeida, M.; Pite, H.; Pereira, A. M.; Todo‐Bom, A.; Nunes, C.; Bousquet, J.; Fonseca, J.
Abstract: Background: Nationwide epidemiologic data on rhinitis in the elderly do not exist. This study aimed to estimate the prevalence of rhinitis in the population aged 65 years or above in mainland Portugal and to characterize and classify rhinitis in this age group. Methods: Cross‐sectional, nationwide, population‐based survey of citizens aged 65 years or above, living in mainland Portugal. Current rhinitis (CR) was defined as the presence of at least two symptoms: 'repeated sneezing and itchy nose', 'blocked nose for more than one whole hour', or 'runny nose when not having a cold or flu', either usually or in the last 12 months. Rhinitis severity was assessed using a visual analogue scale; rhinitis was classified according to ARIA. Results: Data were obtained from 3678 responders (92.5% response rate). The prevalence of CR was 29.8% (95% confidence interval (CI): 28.4%–31.3%): 49.1% had mild intermittent, 7.0% mild persistent, 27.5% moderate‐severe intermittent, and 16.4% moderate‐severe persistent rhinitis. Only 38.6% of patients with CR had been physician diagnosed and 38.7% were under treatment for this disease in the previous year. Allergic conjunctivitis symptoms were referred by 68.6% of subjects with CR (rhinoconjunctivitis population prevalence, 20.5% (95% CI: 19.2%–21.8%)). Conclusions: Rhinitis and rhinoconjunctivitis are common but underdiagnosed and undertreated diseases in the geriatric population. This was the first nationwide epidemiological survey classifying rhinitis according to ARIA guidelines in this age group. More than 40% of old‐age patients presented moderate‐severe disease.